Outcomes in medical admissions with hyponatraemia in Ghana – a single-centre study - Tannor, Elliot Koranteng; Akumiah, Emmanuel Owusu; Norman, Betty R (African Journal of Nephrology, 2019)
Introduction: Hyponatraemia is the most common electrolyte abnormality in hospitalized patients and is associated with poor prognosis and high mortality. There is a paucity of data on hyponatraemia in Ghana. We set out to describe the prevalence of this condition, its associations and the outcomes in terms of in-hospital mortality and length of hospital stay. Methods: We conducted a retrospective study of all admissions from October 2017 to April 2018 on the medical ward at the Komfo Anokye Teaching Hospital (KATH). Demographic information, medical diagnoses as well as clinical and laboratory data were documented. Means (± standard deviation) were recorded for normally distributed data, whereas non-normally distributed data were recorded as medians [interquartile range (IQR)]. Chi-squared and Fisher’s exact tests were used to test categorical variables. ANOVA and Kruskal-Wallis tests were used for the analysis of hyponatraemia severity; a p value of < 0.05 was considered statistically significant. Results: Within the study period, 406 patients with hyponatraemia were identified in 1477 medical admissions, a prevalence of 27.6%. Their mean age was 51.5 ± 19.0 years. There were 217 males (53.5%). The mean serum sodium was 128.7 ± 6.5 mmol/L. Two hundred and forty (59%) had mild hyponatraemia, 106 (26%) had moderate hyponatraemia and 60 (15%) had severe hyponatraemia. The most common associated medical conditions were infections (26%), chronic liver disease (17%), hyperglycaemia (17%), chronic kidney disease (16%) and chronic heart failure (8%). In-hospital mortality was 31.8% and varied with the severity of the hyponatremia. The median length of hospital stay was 7 days (IQR 4–10 days) and did not vary with the severity of hyponatraemia. Mortality was associated with serum sodium concentration (p = 0.007) and lower levels of consciousness (Glasgow Coma Scale, GCS, ≤ 13) at presentation (p < 0.001). Conclusions: Hyponatraemia is common in medical admissions in Ghana, and is mostly associated with infections, and chronic liver, kidney and heart diseases. It is associated with high in-hospital mortality, especially when hyponatraemia is more severe or accompanied by relatively low GCS scores.